2013
DOI: 10.3109/0886022x.2012.760408
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline Protects Against Glycerol-Induced Acute Renal Failure in Rats

Abstract: There is an increasing evidence that oxidative stress plays an important role in the pathogenesis of rhabdomyolysisinduced acute renal failure (ARF). In this study, protective effects of L-citrulline on glycerol-induced ARF in rats were investigated. Six groups of rats were employed in this study: group 1 served as a control; group 2 was only given glycerol (50%, 10 mL/kg, i.m.); group 3 was given glycerol plus dexamethasone (0.1 mg/kg, i.g.) as positive reference drug, starting at the same time as the glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Considering that most reactive oxygen species (ROS) are highly reactive and short‐lived, it is difficult to detect them in biological substances . Therefore, measurement of the end products of lipid peroxidation is one of the most widely accepted approaches for evaluating oxidative damage . 4‐HNE, which is commonly used as a marker of lipid peroxidation, as well as oxidative DNA and/or protein damage, is the major 4‐hydroxyalkenal end product generated by the decomposition of polyunsaturated fatty acids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that most reactive oxygen species (ROS) are highly reactive and short‐lived, it is difficult to detect them in biological substances . Therefore, measurement of the end products of lipid peroxidation is one of the most widely accepted approaches for evaluating oxidative damage . 4‐HNE, which is commonly used as a marker of lipid peroxidation, as well as oxidative DNA and/or protein damage, is the major 4‐hydroxyalkenal end product generated by the decomposition of polyunsaturated fatty acids .…”
Section: Discussionmentioning
confidence: 99%
“…In sepsis‐induced AKI, TNF‐α activates inducible nitric oxide synthase (iNOS), an indicator of inflammation and stress, which lead to excessive nitric oxide (NO) production . The overproduction of iNOS‐derived NO causes kidney tubular injury in glycerol‐induced AKI . Excess NO reacts with superoxide (O 2 − ) to form peroxynitrite (ONOO − ), a presumed source of hydroxyl radicals, thus causing renal tubular damage …”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that in some cell types, the activity of NO is influenced by the endogenous antioxidant GSH [22]. It is conceivable that GSH activity may be augmented by L-citrulline as it has been shown that pre-treatment with L-citrulline in rodents for seven consecutive days lead to an elevation in the level of GSH [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Xing et al and Liu et al reported similar results. 19,20 Many therapeutic agents have been recently used as an attempt to prevent renal damage-induced glycerol, e.g. theophylline, 16 ferulic acid 21 and montelukast.…”
Section: Discussionmentioning
confidence: 99%